The Mali Market - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The Mali Market Information Project (Projet d appui au système du marché agricole PASIDMA) brings together the APCAM Assembly of Chambers of Agriculture of Mali with United States aid and academic support. In addition to setting up networks to...